Effects of Black Garlic (Black Allium sativum) on Creatinine Levels in Tuberculosis-Infected Mice (Mus Musculus) - Hartini, Supri; Andika Sukarya , I Gede; Putri Wasito , Anatasya (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
There is a high prevalence of tuberculosis (TB) in Indonesia, which is the second country with the highest TB cases in the world. Tuberculosis is an infectious disease that can attack various organs of the body and is the main cause of death among other infectious diseases. Garlic (Allium sativum) contains the compound allicin which has high antibacterial activity, equivalent to penicillin and modern antibiotics such as chloramphenicol, so it can be used to prevent and treat various diseases including tuberculosis. This study aims to determine the benefits of black garlic (Black Allium sativum) in controlling creatinine levels in mice (Mus musculus) infected with TB, considering that black garlic is known to have various medical properties including antioxidant, anti-inflammatory and anticancer. The research design used is Quasi-Experimental Design, namely a non-random repeat experimental design carried out with a post-test and having a control group and an experiment determined using a non-random method. The mice used were divided into several groups, including a healthy group, a group infected with tuberculosis, a group that received black garlic treatment, and a group that was given a combination of black garlic + OAT. Mice infected with TB were given black garlic, and creatinine levels were measured to determine the effectiveness of the treatment. A statistical test was carried out using the One Way Anova test on the creatinine levels of a group of tuberculous mice given black garlic. The average creatinine levels in the four treatment groups of mice were within normal limits, with the lowest value being 0.24 mg/dL and the highest value being 0.59 mg/dL. Next, a statistical test was carried out using the One Way Anova test and the results showed a P value of 0.807. This P value>0.05 indicates that the administration of black garlic does not affect creatinine levels in mice infected with tuberculosis.